2003
DOI: 10.1021/es020564y
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination of Polyaromatic Hydrocarbons from Soil by Steam Stripping:  Mathematical Modeling of the Mass Transfer and Energy Requirement

Abstract: For cleaning of contaminated soil from polyaromatic hydrocarbons (PAH), a thermal separation process is applied. The process uses superheated steam that is supplied through a nozzle together with a suspension (approximately 40% soil content) of the contaminated soil into a tube reactor. In the reactor, the soil suspension is vaporized, and the PAH are stripped from the soil at temperatures of 140-300 degrees C. In a cyclone, a solid-vapor separation is carried out, and after going through a condenser, a separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 7 publications
0
12
0
1
Order By: Relevance
“…Few workers have specifically studied the remediation of drill cuttings; however, there has been significantly more research carried out into the treatment of contaminated soils, a system which also contains a mineral phase, water and an organic phase. By far the most common method of soil remediation is gas stripping with a heated gas stream, with Lord (1998) and Braass et al (2003) demonstrating steam stripping for the removal of organic contaminants. Enhanced soil stripping processes have also been reported, with Buettner and Daily (1995) demonstrating an air stripping system which utilised electrical heating of the bulk contaminated soil.…”
Section: Theory Of Microwave Heatingmentioning
confidence: 99%
“…Few workers have specifically studied the remediation of drill cuttings; however, there has been significantly more research carried out into the treatment of contaminated soils, a system which also contains a mineral phase, water and an organic phase. By far the most common method of soil remediation is gas stripping with a heated gas stream, with Lord (1998) and Braass et al (2003) demonstrating steam stripping for the removal of organic contaminants. Enhanced soil stripping processes have also been reported, with Buettner and Daily (1995) demonstrating an air stripping system which utilised electrical heating of the bulk contaminated soil.…”
Section: Theory Of Microwave Heatingmentioning
confidence: 99%
“…The main NAPL recovery mechanisms with steam injection are (Davis, 1998): (i) the physical displacement by the hot water formed from the condensation of steam, and by the steam itself; (ii) the decrease of the interfacial tension and capillary pressure at elevated temperatures that reduces the residual NAPL saturation; (iii)the decrease of NAPL viscosity, which increases its mobility and the efficiency of its displacement by condensed water (She and Sleep, 1998;Gudbjerg et al, 2004a,b); (iv) the volatilization and steam distillation (Tzovolou et al, 2010); (v) the transport of contaminant vapor in the steam phase (steam stripping) to a condensation front where accumulated light hydrocarbons assist in the reduction of interfacial tension, capillary pressure, and viscosity with similar effect as noted in mechanisms (ii) and (iii). Enhanced desorption of contaminants from the solid surface at elevated temperatures may also occur (Braass et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of numerical models of different complexity and accuracy have been suggested to simulate steam injection in soils (Shoda et al, 1998;Kuhlman, 2002;Gudbjerg et al, 2004b;Braass et al, 2003;Tse et al, 2006). Experimental and theoretical studies revealed that steam injection is an efficient method of soil remediation for mixtures of volatile and semi-volatile contaminants with low solubility in water (Sleep and McClure, 2001;Schmidt et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The static sorption behavior of PAHs onto soil/sediment has been described by three models. They are the linear model [6,7], the Freundlich model [8,9] and the Langmuir model [10,11]; and these models were evaluated under different situations [12,13]. Salinity was found to be one of the significant factors affecting the biodegradation of PAHs [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%